REAKSI PASAR SAHAM TERHADAP PENGUMUMAN PERUBAHAN PERINGKAT OBLIGASI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA SELAMA PERIODE 2016-2018 - Miranti Makatita; Abdul Wahid Mahsuni; Afifudin Afifudin (Universitas Islam Malang, 2019)
ABSTRACT The capital market is one of the most important factors for an industrial country that is both developing and advanced, one of the functions of the capital market is to become a benchmark for the progress of the economy of one country. if the capital market owned by a country, its growth and development improves then it can be ascertained that one country's economic stability is also good. This study aims to empirically examine the effect of stock market reactions which include stock returns and abnormal returns to changes in the announcement of bond ratings both before, now, and after the companies listed on the Indonesian stock exchange. The sample used was 35 using purposive sampling, the type of research using non-experimental, data collection techniques in this study using observation techniques and the data used in the form of secondary data and analytical methods used include morality tests and hypothesis testing. The results of data analysis show that stock returns do not have a significant difference to before, during, and after the announcement of bond ratings, abnormal stock returns have a significant difference to before, during, and after the announcement of bond ratings.Keywords: capital markets, stock returns, abnormal returns, and bond ratings.